Investigating thrombocytopenia in Meropenem-treated patients: a cross-sectional observational study - Ahmed E. Altyar; Sairah Hafeez Kamran; Hira Batool; Zikria Saleem; Noor Shahid (Future Journal of Pharmaceutical Sciences)
Abstract Meropenem is frequently employed empirically to treat both single and polymicrobial infections. In clinical practice, meropenem injections have been shown to induce thrombocytopenia. The main aim of this study was to examine the incidence of thrombocytopenia following administration of a standardized dose of meropenem. This cross-sectional observational study was conducted at a tertiary care hospital from January 1, 2022, to July 15, 2022. This study included 210 patients admitted to intensive care unit. The patient received a typical dose of meropenem depending on age (300–2000 mg) and had no prior medical history of blood dyscrasias. Thrombocytopenia was observed in 59.5% of subjects who were administered a standard dose of meropenem. Absolute thrombocytopenia was noted in 24.7% of the patients, whereas relative thrombocytopenia was detected in 34.8%. Additionally, 41.5% of the participating patients exhibited no alteration in platelet count. Statistical analysis revealed no significant association between sex and meropenem-associated thrombocytopenia (P = 0.522). Meropenem-induced thrombocytopenia didn’t correlate with age in patients undergoing combination therapy (P = 0.586) or monotherapy (p = 0.615). A significant correlation (p < 0.05) was observed between the dosage (300 mg–3 g) and duration of medication use and thrombocytopenia. The odds ratio indicated an elevated probability of patient fatalities in the single therapy group. This study suggests that thrombocytopenia may arise during meropenem treatment, suggesting that it is a potential adverse effect for physicians and pharmacists to consider during therapy.